ZrO2 thin films on Si substrate - Wong, Y.H.; Cheong, K.Y. (Kluwer (now part of Springer), 2010)
In the advancement of metal–oxide–semiconductor technology, Si-based semiconductor, with SiO2 as outstanding dielectric, has been dominating microelectronic industry for decades. However, the drastic down-scaling in ultra-large-scale integrated circuitry has made ultrathin SiO2 (~1.2 nm) unacceptable for many practical reasons. Introduction of ZrO2 as high-κ dielectrics replacing SiO2 is undeniably a potential yet formidable solution for the aforementioned problem. The objective of this review is to present the current knowledge of ZrO2 thin film as gate dielectric on Si, in terms of its material and electrical properties produced by various deposition techniques. One of the techniques being focused is thermal oxidation of sputtered Zr and the mechanisms of transforming the metal into oxide has been extensively reviewed.